2022
DOI: 10.1186/s13048-022-01064-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oocyte vitrification using a semi-automated or a manual closed system in human siblings: survival and transcriptomic analyses

Abstract: Background Indications of oocyte vitrification increased substantially over the last decades for clinical and ethical reasons. A semi-automated vitrification system was recently developed making each act of vitrification reproducible. In this study, we evaluated the efficiency of the semi-automated technique of oocyte vitrification by survival rate, morphometric assessment and resistance to empty micro-injection gesture as compared with a manual method. Additionally, we intended to evaluate tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…All the altered pathways in our study are directly related to the cell cycle, meiosis, and cell division [ 84 , 85 , 86 ], which are the main pathways distorted in vitrified oocytes in humans [ 75 ] and cows [ 52 , 53 ]. Other pathways related to mRNA and RNA catabolic processes and membrane-bound and intracellular organelles were affected after the vitrification of human [ 49 ] and bovine oocytes [ 53 ], which coincide with the clusters found in VIM vs. VMAT, where the metabolic process and transcription initiation in the biological function and the polymerase complex and organelle membrane in the cell component were affected. Remarkably, pathways related to calcium and ion transport, which were common in our three comparisons, have not been mentioned in other studies, except in cumulus cells after vitrification in porcine oocytes [ 55 ].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…All the altered pathways in our study are directly related to the cell cycle, meiosis, and cell division [ 84 , 85 , 86 ], which are the main pathways distorted in vitrified oocytes in humans [ 75 ] and cows [ 52 , 53 ]. Other pathways related to mRNA and RNA catabolic processes and membrane-bound and intracellular organelles were affected after the vitrification of human [ 49 ] and bovine oocytes [ 53 ], which coincide with the clusters found in VIM vs. VMAT, where the metabolic process and transcription initiation in the biological function and the polymerase complex and organelle membrane in the cell component were affected. Remarkably, pathways related to calcium and ion transport, which were common in our three comparisons, have not been mentioned in other studies, except in cumulus cells after vitrification in porcine oocytes [ 55 ].…”
Section: Discussionmentioning
confidence: 53%
“…Whereas a first study in mice [ 51 ] showed minor or no changes in the transcriptome, a recent study reported 4747 DE genes [ 50 ]. Similarly, in humans, Monzo et al (2012) [ 48 ] found 608 DE genes using GeneChip arrays, and later, Huo et al (2021) [ 75 ] and Barberet et al (2022) [ 49 ] found notable differences, with a total of 1987 and 108 DE genes, respectively, using single-cell RNA-seq. In pigs and cattle, comparisons were made between fresh in vitro matured and oocytes vitrified at the GV stage followed by in vitro maturation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, throughout growth and maturation, oocytes are exposed to multiple environmental stressors, which can alter the sequential gene expression changes governing oocyte development [ 56 ]. Our identification of transcripts expressed along oocyte development that are highly susceptible to those factors is of major importance, as they may be the key to understanding the apparition of oocyte defects and deficiencies and overcoming these outcomes [ 27 , 28 , 29 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. For oocyte in vitro maturation and cryoconservation, regaining expected levels of expression of those transcripts by adapting assisted reproductive protocols may become a path of research to increase mature oocyte rates in the future.…”
Section: Discussionmentioning
confidence: 99%